THE DEATH OF GOD AND THE UNIMAGINABLE ESSENCE OF CONTEMPORARY EDUCATION: A POSTMETAPHYSICAL CRISIS IN TEACHING HUMANITIES AND ARTS - Panasiuk, Mariia (Collection of scientific papers «ΛΌГOΣ», 2025)
Introduction: The Decline of the Sacred in the Educational Sphere. Friedrich Nietzsche’s proclamation of the death of God in The Gay Science (1882) resonates throughout contemporary debates on the crisis of modern education, particularly in the fields of humanities and arts. This death symbolizes not merely the decline of religious belief but the erosion of metaphysical structures that once underpinned the legitimacy of knowledge, culture, and values. In our neoliberal epoch, education is increasingly functionalized, stripped of metaphysical depth, and subsumed into economic logics that reduce knowledge to marketable skills. In the humanities and arts, where education once engaged deeply with questions of existence, morality, and meaning, this crisis is felt acutely.